Atmospheric controlled processing enabling highly textured NKN with enhanced piezoelectric performance. Issue 4 (April 2019) - Gao, Lisheng; Dursun, Sinan; Gurdal, A. Erkan; Hennig, Eberhard; Zhang, Shujun; Randall, Clive A.
Abstract: High-performance lead-free piezoelectrics are of interest as alternate materials to confront potential legislative actions on lifting the exemption on lead-based piezoelectric materials. In this work, we demonstrated a highly textured commercial-grade Li- and Ta- modified (Na, K)NbO3 (NKN) lead-free piezoceramic that was sintered under low oxygen partial pressure ( pO 2 ) atmospheres using the solid state template grain growth (TGG) method. It was found that a moderate low pO 2 condition not only facilitated the reactive template grain growth but also lowered the temperature required for such process. Highly textured NKN with a converse piezoelectric coefficient d 33 * ≈ 680 p m V - 1 was obtained, this remarkable piezoelectric property can be explained by the position of the polymorphic phase boundary of NKN. With considerations on both performance and cost, this work not only presented the potential for NKN to meet the requirement of commercial applications, but also provided an effective processing strategy to utilize low cost base metal inner electrodes in the future.